Living Traditions and Universal Conviviality: Prospects and Challenges for Peace in Multireligious Communities - Faber, Roland; Slabodsky, Santiago (Lexington Books, 2016)
The World Parliament of Religions adopted the view that there will not be peace in this world without including peace among religions. Yet, even with the unified force of the world’s religions and wisdom traditions, this cannot be accomplished without justice among people. In one way or another, “unity” among religions, as based on justice and the will to accept the other’s religions and even irreligiosity as means of justice, will not prevail without an internal and external, spiritual, theological, philosophical and practical investigation into the very reasons for religious strife and fanaticism as well as the resources that people, cultures, religions and wisdom traditions might provide to disentangle them from the injustices of their host regimes, and to seek the “balance” that leads to a measure of universal fairness among the multiplicity of religious and non-religious expressions of humanity. “Conviviality” expresses the depth and breadth of “living together,” which itself can be understood as a translation of a central term of Whitehead's philosophy and the process tradition—“concrescence” (growing together, becoming concrete)—as it is recently and increasingly used in different discourses to name the concrete community of difference of individuals, cultures, and religions in appreciation of the mutual inclusiveness of their lives. This book seeks to bring together experts from different religious (and non-religious) traditions and spiritual persuasions to suggest ways in which the living wisdom traditions might contribute to, and transform themselves into, a universal conviviality among the people, cultures and religions of this world for a common future. It wishes to test the resources that we can contribute to this concurrent and urgent matter, aware of Whitehead's call for a radical transformation of power and violence in thought and action as, perhaps, the ultimate theory of conflict resolution.